Medication errors in emergency departments: is electronic medical record an effective barrier? - Vaidotas,Marina (2019)
ABSTRACT Objective: To compare medication errors in two emergency departments with electronic medical record, to two departments that had conventional handwritten records at the same organization. Methods: A cross-sectional, retrospective, descriptive, comparative study of medication errors and their classification, according to the National Coordinating Council for Medication Error Reporting and Prevention, associated with the use of electronic and conventional medical records, in emergency departments of the same organization, during one year. Results: There were 88 events per million opportunities in the departments with electronic medical record and 164 events per million opportunities in the units with conventional medical records. There were more medication errors when using conventional medical record – in 9 of 14 categories of the National Coordinating Council for Medication Error Reporting and Prevention. Conclusion: The emergency departments using electronic medical records presented lower levels of medication errors, and contributed to a continuous improvement in patients´ safety.